An integrated numerical framework to investigate the running safety of overlong freight trains. (January 2021) - Krishna, Visakh V; Jobstfinke, Daniel; Melzi, Stefano; Berg, Mats
Long freight trains up to 1500 m in length are currently not in regular operation in Europe. One of the important reasons for the same is high inter-wagon forces generated during the operation, especially when pneumatic (P-type) brake systems are used. For long trains with multiple locomotives at different positions along the train, radio communication with necessary fail-safe mechanisms can be used to apply the brakes. Long freight train operation on a given line is subjected to various attributes such as braking/traction scenarios, loading patterns, wagon geometries, brake-block materials, buffer types, track design geometries, etc., which are referred to as heterogeneities. The complex longitudinal train dynamics arising in the train due to various heterogeneities play a major role in determining its running safety. In this context, the maximum in-train force refers to the maximum force developed between any two wagons along the train during operation. The tolerable longitudinal compressive force is the maximum compressive force that can be exerted on a wagon without resulting in its derailment. Here, the authors adopt a bottom-up approach to model pneumatic braking systems and inter-wagon interactions in multibody simulation environments to study the complex longitudinal train dynamics behavior and estimate maximum in-train forces and tolerable longitudinal compressive forces, subjected to various heterogeneities. These two force quantities intend to facilitate a given freight train operation by providing guidelines regarding the critical heterogeneities, that currently limit its safe operation. In doing so, the authors propose the notion to have an operation-based approval for long freight trains using the simulations-based tool.